Output Characteristics of a GaAs Photoconductive Semiconductor Switch With Comb Electrodes - Yong Pyo Kim; Pyeung Hwi Choi; Jongbae Kang; Sung-Min Hong; Sungbae Lee; Jae-Hyung Jang (IEEE Access)
GaAs photoconductive semiconductor switches (PCSSs) with comb electrodes were fabricated on semi-insulating GaAs. A pulsed 1064-nm laser with a 700-ps (FWHM) pulse width and optical energy of $134 \; μ $ J was used to trigger 2-mm-gap PCSSs with comb lengths ranging from 0 to $750 \; μ $ m. The effect of the comb electrodes on the output characteristics was investigated by comparing the performance parameters of sample devices with different comb lengths. Devices with a longer comb exhibited higher peak output voltage and better immunity against surface flashover. A PCSS specimen with a 750- $μ $ m comb exhibited a higher peak output voltage by 3.53 times compared to a PCSS without a comb at bias voltages lower than 1 kV. Moreover, the PCSS with the 750- $μ $ m comb electrode successfully generated a pulse with a peak voltage of 1.34 kV, while the peak voltage generated by a PCSS without a comb was limited to 0.74 kV.